(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
Philosophy as the mother of all disciplines, reflects on the events that happen around the human being, the philosophy of science, meanwhile, deals with the relationship between the scientific ethos and its knowledge. Scientific theories allow man (anthropologically understood) to understand the phenomena to which we are exposed and give validity to the arguments that are closest to the reality of the facts. This paper reviews the controversy between realists and anti-realists about the " no-miracle argument" (miracles argument, in Spanish) raised by Hilary Putman.